Molecular structure, infrared spectra, and photochemistry of isoniazid under cryogenic conditions - Borba, Ana (2009)
In this study, the structure, spectroscopy, and photochemistry of isoniazid (C6H7N3O, INH) were studied by low-temperature infrared spectroscopy and quantum chemistry calculations. According to DFT(B3LYP)/6-311++G(d,p) calculations, 12 minima were found on the potential energy surface of the molecule, corresponding to two cis conformers about the O=C-N-N axis (C1, C2) and one form trans about this axis (T), all being 4-fold degenerate by symmetry. The C1 conformer was predicted to be more stable than T and C2, by 20.4 and 22.6 kJ mol(-1), respectively. In consonance with these results, only C1 could be observed in low-temperature argon and xenon matrixes as well as in the neat glassy state prepared from the vapor of the compound at 70 degrees C. The C1 conformer was also found to be the constituting monomeric unit of the crystalline phase of INH produced from warming of the low-temperature neat amorphous state. The infrared spectra of INH in the different phases studied were fully assigned. After UV (lambda > 235 nm) irradiation of the matrix-isolated isoniazid, the compound was found to undergo photolysis through two different pathways: a Norris type I alpha-cleavage leading to production of isonicotinaldehyde and N2H2 and a concerted sigmatropic reaction with production of pyridine, CO and N2H2. The latter reaction was found to be nearly two times faster than the former in both argon and xenon matrixes. In addition, both reactions were found to be disfavored in a xenon matrix, which is in consonance with the involvement of (n, pi*) excited states in both photochemical processes.